Distribution of the dissolved oxygen and aou in the atlantic water of the Arctic ocean - A. P. Nedashkovsky; N. I. Savelieva; O. A. Morozova; L. A. Timokhov; А. П. Недашковский; Н. И. Савельева; О. А. Морозова; Л. А. Тимохов (Journal of Geophysical Research, 2016)
The results of hydrochemical study received during drift of SP-34 and SP-35 stations, and also oceanographic supervision in high-latitude Arctic expeditions 2005 and 2007 are presented. Variability of distribution of the dissolved oxygen and apparent oxygen utilization (AOU) in a core of the Atlantic water mass (AWM) in theEurasianBasinis investigated. Distribution of oxygen in a core of AWM is characterized by its almost constant contents in Amundsen andNansenBasinsand over Gakkel Ridge. Vertical distribution of oxygen in hollows is characterized by a minimum in a core of the Atlantic waters.It is shown that there is a relation between the water temperature in the core of AWM and AOU in the studied area — with reduction of water temperature apparent oxygen utilization increases.The smallest AOU is observed in AWM coming fromFramStraittoNansenBasin. Along the Eurasian continental slope AOU in a core of AWM increases, also the greatest its value has return Atlantic waters inAmundsenBasin. The possible scenarios explaining transformation of characteristics of a core of AWM extending along the Lomonosov Ridge are discussed.Apparent oxygen utilization in a core of AWM has significant variations of sizes in Nansen andAmundsenBasinsand unlike the size of the dissolved oxygen which variability is small, can serve as the good indicator of transformation and circulation of the Atlantic waters in theEurasianBasin. Представлены результаты гидрохимических исследований, полученные во время дрейфа станций СП-34 и СП-35, а также океанографических наблюдений в высокоширотных арктических экспедициях 2005 и 2007 гг. Исследована изменчивость растворенного кислорода и дефицита кислорода в ядре атлантической водной массы (АВМ) в Евразийском суббассейне. Распределение кислорода в ядре АВМ характеризуется практически постоянным его содержанием в котловинах Амундсена и Нансена и над хребтом Гаккеля. Вертикальное распределение кислорода в котловинах характеризуется минимумом в ядре атлантических вод.Показано, что в исследуемом районе ...